Bridging the ICT Gap: TOGAF ADM's Role in Modernizing Educational Institutions (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2024)
In the rapidly advancing world of Information and Communication Technology (ICT), various industries have recognized and started to harness technology's transformative power, especially when it comes to data management and processing. One significant component of this technological evolution is Enterprise Architecture (EA). This offers a structured framework for integrating vast amounts of data across large-scale systems. However, an area that remains somewhat untapped is the application of EA within the educational sector, which presents its own unique set of ICT challenges. This research seeks to address and bridge this knowledge gap. It takes an in-depth look at how EA, utilizing the TOGAF ADM framework, can be implemented in educational settings. Through a series of structured interviews conducted at SMA St. Bellarminus, the research aims to tailor the institution's information systems architecture to its specific and nuanced needs. While there have been previous studies that touched upon organizational systems and structures, our research distinguishes itself by modifying and adapting the TOGAF ADM approach to cater explicitly to educational environments. As the digital realm continues to expand and evolve, it's imperative for educational institutions to have the tools and methodologies in place to stay relevant and efficient in this ever-changing landscape.